2023
DOI: 10.1186/s13244-023-01386-w
|View full text |Cite
|
Sign up to set email alerts
|

Does deep learning software improve the consistency and performance of radiologists with various levels of experience in assessing bi-parametric prostate MRI?

Abstract: Objective To investigate whether commercially available deep learning (DL) software improves the Prostate Imaging-Reporting and Data System (PI-RADS) scoring consistency on bi-parametric MRI among radiologists with various levels of experience; to assess whether the DL software improves the performance of the radiologists in identifying clinically significant prostate cancer (csPCa). Methods We retrospectively enrolled consecutive men who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, in a study by Liu et al [57], which conducted an evaluation method based on textural classification, a sensitivity of 0.85 and a specificity of 0.73 were found in demanding PIRADS = 3. On the other hand, Arslan et al [58] reported no clear benefit from the use of deep learning software in studies carried out at different levels of experienced radiologists. Compared to similar works undertaken by Gianni [59,60], obtaining a correct classification F1-score greater than 76% is a good result for texture features attributed to different lesions assigned to PIRADS.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study by Liu et al [57], which conducted an evaluation method based on textural classification, a sensitivity of 0.85 and a specificity of 0.73 were found in demanding PIRADS = 3. On the other hand, Arslan et al [58] reported no clear benefit from the use of deep learning software in studies carried out at different levels of experienced radiologists. Compared to similar works undertaken by Gianni [59,60], obtaining a correct classification F1-score greater than 76% is a good result for texture features attributed to different lesions assigned to PIRADS.…”
Section: Discussionmentioning
confidence: 99%